Prästgårdsträdgårdar : barndomsskildringar från 14 prästgårdsträdgårdar i Växjö stift - Franzén, Emma (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Few rectory gardens are today remaining in their former design and the cultural heritage that they represent are disappearing. Since 1987-88 the parishes are no longer bound to keep housing for their priests, which means that they, for economical reasons, are starting to sell their rectories. With this in mind, a group of people, growing up in rectories in Småland and Öland between the 1930th and 1950th, formed an interest group to save the memory of their rectory gardens. On the basis of their memories, they have written a couple of descriptions of the rectories, which describe the gardens content, design and the life they once lived there. With this compilation of the 14 rectory gardens I want to keep the memory of them and create a ground for future work in this field.